WETON SEBAGAI SYARAT PERNIKAHAN PERSPEKTIF HUKUM ISLAM - M. Abdul Aziz Dawaamu Aliyuddiin; Dzulfikar Rodafi; Dwi Ari Kuriniawati (Jurnal Hikmatina, 2022)
AbstrakMany Javanese people believe that weton is a sacred birthday that can be counted and determines the future. The focus and purpose of this study is to find out what is meant by Weton, Weton's calculations for marriages that occur in Srimulyo Village and Weton As Marriage Conditions from an Islamic Law. This research uses a qualitative approach with a descriptive case study type. Sources of data in this study is from observations, interviews and documentation. The results of this study found that weton is the day of birth based on the Javanese calendar. The method of calculating weton as a requirement for marriage in Srimulyo Village is to start by calculating the birth weight of a person and then adding up the birth weights of a pair of prospective brides and grooms. There is a separate forecast for the future based on the results of the sum. In Islamic law, basically a custom is permissible, but the use of weton as a marriage requirement which is the custom of the Srimulyo Village community in determining a potential partner is a form of polytheism because it is accompanied by beliefs and worries about future predictions. Keywords: Weton, Custom, Islamic Law